Enhancing Biology Teachers' Knowledge on Blood Groups and Transfusion - Tanzillia, May Fanny; Adrianto, Hebert; Handayani, Lidya; Tandean, Victor Setiawan; Banjarnahor, Dharma Putra Perjuangan; Keith, Jennifer (STMIK Widya Cipta Dharma, 2025)
Knowledge of blood types and blood transfusion is crucial in daily life. Knowing one’s own blood type is important because it can provide necessary information for blood transfusions for patients who are in critical need of blood. Biology teachers need to strengthen their understanding of the concepts to ensure they have sufficient scientific knowledge and avoid misconceptions when teaching biology topics to students. There have not been many concept strengthening activities between teachers and the Faculty of Medicine. The goal of this community service is to deepen the understanding of blood types and blood transfusion concepts among biology teachers in the Ciputra group. The participants in this activity are biology teachers from the Ciputra group. The activity was held on October 17, 2024, via Zoom. The equipment used for this activity includes laptops connected to Wi-Fi, Google Drive for storing PowerPoint (PPT) materials and videos, and Google Forms for pre-tests and post-tests. The material that was deepened in this session is blood types and blood transfusion. The results of the pre-test and post-test were analyzed descriptively. The results show that the school fully supported this learning activity. The speaker for this activity was a clinical pathology specialist and lecturer. The results of the activity indicate a slight improvement in the average scores of the pre-test and post-test. Overall, the activity ran according to plan. The material should be repeated, but presented with a different learning method. Further deepening of medical biology material should continue with other topics. Teachers need to adapt to the level of medical material and should engage in self-learning before the activity begins.